Research on the Application of BIM Digitalization and Intelligence in Economic Management in the Construction Industry - Yang, Qisheng (Journal of Innovative Studies, 2024)
With the rapid advancement of information technology, the construction industry is undergoing a profound technological revolution. The advent of Building Information Modeling (BIM) technology marks the beginning of this transformation, which has not only changed the way of design and construction but also brought revolutionary impacts to engineering management. This study aims to explore the application of BIM technology in economic management in the construction industry, analyze its impacts and benefits, as well as the challenges and development prospects it faces. The construction industry, as a vital component of the national economy, plays a significant role in economic growth. The increasing demands for environmental protection and functionality have rendered traditional two-dimensional design and management methods inadequate for modern building projects. BIM technology, with its unique three-dimensional visualization and information management capabilities, offers new solutions for construction and management. The application of BIM technology can optimize the economic management of building projects on multiple levels. Firstly, it enhances the accuracy of design and construction efficiency. Through the construction of three-dimensional models, designers and engineers can more intuitively understand design intentions and engineering details, thereby reducing the costs and time associated with design changes and rework. Secondly, BIM technology optimizes resource allocation and cost control. By dynamically managing the model, it is possible to monitor cost and resource usage, enabling more precise cost control and risk management. Additionally, BIM technology also facilitates the efficiency of information sharing and collaboration in projects. By establishing a unified information platform, all parties involved in the project can communicate and collaborate more efficiently, shorten the project cycle, and reduce communication costs. However, the application of BIM technology in economic management within the construction industry also faces some challenges. For instance, the promotion and application of BIM technology require corresponding talent support and technical training, which poses a significant challenge for many enterprises. Moreover, the implementation of BIM technology necessitates investment in both hardware and software facilities, potentially impacting the financial status and business decisions of enterprises. The significance of this study lies in its in-depth analysis of the effectiveness and potential of BIM, providing strategies and recommendations for enterprises to implement BIM, promoting the widespread application of BIM technology in the construction industry, and driving technological progress and economic benefits in the industry. Simultaneously, this study will also provide theoretical support and practical references for the formulation of relevant policies and the establishment of industry standards, thereby promoting the healthy development of the construction industry.